Konsep Pendekatan Multi-Mekanisme untuk Tata Kelola TI di Institusi Pendidikan Tinggi Indonesia - Anwar Fattah; Mayda Waruni Kasrani; Khairunnisa Nurhandayani; Diah Patriana Setianingsih (Lembaga Penelitian Universitas Balikpapan, 2024)
This study aims to explore a multi-mechanism approach to IT governance in Indonesian higher education institutions. It examines the various factors and strategies involved in effective IT governance within the context of Indonesian academia. The objective of this article is to collect and analyze the different factors that influence the implementation of an IT Governance model in Indonesian higher education institutions. Through a literature review methodology, the study identifies 5 factor core mechanism and 4 factor additional mechanism that influence the implementation of IT governance in Higher Education Institution. These factors must be taken into account and given special attention for the successful implementation of an IT governance framework.